Genetic Variants in Rare Ophthalmological Syndromes: Novel COL11A1 Splice Site Variant in a Brazilian Family with Stickler Syndrome Type 2 - Pedro Filipecki Mansilla; Vagner Loduca Lima; Gustavo Henrique Araújo Salomão; Denise Maria Christofolini (Journal of Current Ophthalmology, 2024)
Purpose: To genetically investigate a family with a clinical and ophthalmological phenotype suggestive of Stickler syndrome (STL) and the association of molecular findings with ophthalmological, clinical characteristics, and family history. Methods: Specialized ophthalmologic evaluation using diagnostic methods such as fundoscopy, slit-lamp photography, and ocular biometry to describe the phenotypic characteristics of the index patient and family members. Genetic evaluation with genome sequencing (WGS) is to describe the genotypic characteristics of the proband and confirmation of the finding by family-specific variant sequencing (NGS). Results: Genetic evaluation demonstrated the presence of a novel pathogenic variant NM_001854.4: C.3168+1G>A (chr1:102961865-102961865), in the intronic region that follows exon 41 of the COL11A1 in the three affected members of the family. This variant is located 1 base from the natural splicing region of this exon and consequently can impact intron removal and protein formation. As for the ophthalmological findings, the presence of low visual acuity, high axial myopia, and pathological vitreous gel with a “beaded” appearance was observed in the index case. Further clinical examination showed that other family members also had vitreous and retinal degeneration. Conclusions: A heterozygous novel pathogenic variant in COL11A1 was identified by complete genome sequencing in a Brazilian family with STL. Ocular examination findings photographically presented confirm the characteristic features of STL type 2.